Domesticating online games for preteens – discursive fields, everyday gaming, and family life. Issue 2 (4th March 2017) - Willett, Rebekah
Abstract : This article examines families' everyday practices connected with online games played by children ages seven to eleven in the USA. Based on interviews in homes with children and parents, the article employs domestication theory to account for social experiences and symbolic meanings of games and game devices within private and public contexts of children's game play. The analysis focuses on the social process through which online games are brought into home environments and incorporated into families' daily routines. Games are analyzed as both impacting on everyday practices of the family and being shaped by the histories, values, and relationships within the households. The article contributes to an understanding of preteens' online gaming and highlights the strength of using domestication theory to investigate children's media practices.